Alterations of Brain Structural Network in Parkinson’s Disease With and Without Rapid Eye Movement Sleep Behavior Disorder - Guo, Tao; Guan, Xiaojun; Zeng, Qiaoling; Xuan, Min; Gu, Quanquan; Huang, Peiyu; Xu, Xiaojun; Zhang, Minming (Frontiers in Neurology, 2018)
Background and Objective: Rapid eye movement sleep behavior disorder (RBD) has a strong association with alpha synucleinpathies such as Parkinson’s disease (PD), and PD patients with RBD tend to have a poorer prognosis. However, we still know little about the pathogenesis of RBD in PD. Therefore, we aim to detect the alterations of structural correlation network in PD patients with and without RBD. Materials and methods: A total of 191 PD patients, including 51 with possible RBD and 140 non-possible RBD, and 76 normal controls were included in the present study. Structural brain networks were constructed by thresholding gray matter volume correlation matrices of 116 regions and analyzed using graph theoretical approaches. Results: There was no difference in global properties among the three groups. Significant enhanced regional nodal measures in limbic system, frontal-temporal regions and occipital regions and decreased nodal measures in cerebellum were found in PD patients with possible RBD compared with PD patients without possible RBD. Besides, nodes in frontal lobe, temporal lobe and limbic system were served as hubs in both two PD groups, and PD patients with possible RBD exhibited additionally recruited hubs in limbic regions. Conclusion: Based on the structural correlation network analysis, we found PD patients with possible RBD exhibited a reorganization of nodal properties as well as the remapping of the hub distribution in whole brain especially in limbic system, which may shed light to the pathophysiology of PD with RBD.